Magnetic core alloy material, preparation method thereof and magnetic alloy product
By adjusting the element composition and ratio of Fe, Si, B, Nb, Cu, Co, Ni and Mo in the core alloy material, the problem of insufficient magnetic permeability of existing magnetic materials is solved, and the production of high-performance core alloy materials is realized, simplifying the preparation process and reducing costs.
Patent Information
- Application Number
- CN202411628194.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-11
AI Technical Summary
The magnetic permeability of existing magnetic materials is not high enough, which makes it impossible to meet the needs in some application scenarios with high performance requirements. At the same time, the existing preparation methods are complex, costly and difficult to accurately control the performance parameters of magnetic materials.
A magnetic core alloy material is provided, and its elemental composition includes Fe, Si, B, Nb, Cu, Co, Ni and Mo. Through the coordination of specific proportional relationships, the magnetic characteristics are strengthened, the magnetic induction strength and magnetic permeability are enhanced, and the production of high-performance magnetic core alloy material is realized through a simplified preparation process.
The high magnetic induction strength, magnetic permeability and alloy strength of magnetic core alloy materials are achieved, with good uniformity, and the preparation process is simplified, cost is reduced, and it is adapted to the existing production process.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of magnetic material production, and in particular to a magnetic core alloy material and a preparation method thereof, and a magnetic alloy product. Background Art
[0002] With the continuous advancement of electronic technology, electronic equipment and systems are developing towards high frequency, miniaturization and lightweight.
[0003] In the manufacture of modern electronic devices such as transformers and inductors, magnetic core alloy materials play a vital role. The magnetic permeability of the magnetic core alloy material directly affects the performance of the device, such as energy conversion efficiency, inductance, etc. However, the magnetic permeability of the commonly used magnetic materials is not high enough, which leads to the inability to meet the needs in some application scenarios with high performance requirements. For example, the commonly used magnetic material ferrite is a ferromagnetic material. It is generally large in size when used. The resistivity of ferrite is very high, and the energy loss increases, which limits the development of electronic equipment towards miniaturization and high efficiency. In addition, some existing preparation methods are either complicated and costly, or it is difficult to accurately control the performance parameters of the magnetic material, which further restricts the widespread application of magnetic core alloy materials.
[0004] Therefore, the traditional technology still needs to be improved. Summary of the invention
[0005] Based on this, it is necessary to provide a magnetic core alloy material and a preparation method thereof, and a magnetic alloy product. The magnetic core alloy material of the present application has high magnetic induction intensity, magnetic permeability and alloy strength, and has good uniformity.
[0006] This application is implemented through the following technical solutions:
[0007] One aspect of the present application provides a magnetic core alloy material, wherein the element composition of the magnetic core alloy material, measured by atomic mass percentage, comprises:
[0008] Fe 60%~70%;
[0009] Si 14%~18%;
[0010] B 7%~12%;
[0011] Nb 2%~6%;
[0012] Cu 0.3%-2%;
[0013] Co 1%~4%;
[0014] Ni 1%~2%;
[0015] Mo 1%~2%.
[0016] In some embodiments, the element composition of the magnetic core alloy material includes, by mass percentage:
[0017] Fe 64%~68%;
[0018] Si 15%~16%;
[0019] B 9%~11%;
[0020] Nb 3%~5%;
[0021] Cu 0.5%-2%;
[0022] Co 2%~3%;
[0023] Ni 1.5%~1.8%;
[0024] Mo 1.5%~1.8%.
[0025] In some embodiments, the magnetic core alloy material is a nanocrystalline soft magnetic alloy material; when the frequency changes from 1 kHz to 10 kHz, the magnetic permeability change rate of the magnetic core alloy material is less than 0.5%.
[0026] In some embodiments, the steps include:
[0027] Weighing raw materials according to the element composition ratio of the magnetic core alloy material and placing them in a smelting furnace for a first smelting treatment, and casting to obtain an alloy ingot;
[0028] After the alloy ingot is cooled, a second smelting treatment is performed to obtain an alloy melt; the temperature of the second smelting treatment is lower than the temperature of the first smelting treatment;
[0029] The alloy melt is formed and cooled to obtain an alloy strip;
[0030] The alloy strip is subjected to heat treatment and magnetization treatment during the heat treatment process to obtain a magnetic core alloy material.
[0031] In some embodiments, the conditions of the first smelting treatment are: smelting at a vacuum degree of 0.5Pa-0.8Pa and a temperature of 1450°C-1550°C for 2h-4h.
[0032] In some embodiments, the temperature of the second smelting process is 1100° C. to 1250° C.;
[0033] And / or, the time of the second smelting treatment is 50min~60min.
[0034] In some embodiments, the thickness of the alloy strip is 15 μm-20 μm, and the width of the alloy strip is 5 mm-30 mm.
[0035] In some embodiments, the heat treatment step comprises the following steps:
[0036] First, in a vacuum state, heat to 460℃~480℃ and keep warm for 1.5h for pretreatment;
[0037] The magnetization treatment is carried out at a temperature of 460°C to 480°C, and the magnetization time is 60min to 120min;
[0038] Carry out the first heating treatment, raise the temperature to 500℃~550℃, and keep it for 1h~3h;
[0039] Carry out the second heating treatment, raise the temperature to 560℃~580℃, and keep it for 1h~3h.
[0040] In some embodiments, the heating rate during the first heating treatment is (5-10)°C / min;
[0041] And / or, the heating rate during the second heating treatment is (5-10)°C / min.
[0042] The elements of the magnetic core alloy material of the present application include specific components with specific proportions, wherein iron is the main basic element constituting the magnetic core alloy material and is the main source of magnetism; the addition of silicon to the magnetic core alloy material helps to improve the magnetic permeability; boron can play a role in refining grains during the solidification process of the material; copper interacts with other elements and can promote the growth of grains during the heat treatment or solidification process of the material; niobium has the function of refining grains in the magnetic core alloy material; cobalt is an element with high magnetic permeability, and when added to the magnetic core alloy material, it can synergize with elements such as iron to further improve the overall magnetic permeability of the material; nickel and molybdenum are added, and the nickel element can form a stable oxide film on the surface of the alloy to prevent further corrosion. Nickel is also a magnetic element, and synergistically with iron, cobalt, etc., it can enhance the overall magnetism of the magnetic core alloy material and improve the magnetic permeability. An appropriate amount of molybdenum content can enhance the magnetic properties, and nickel and molybdenum can also improve the physical properties of the material. The components enhance the magnetic properties, enhance the magnetic induction intensity and magnetic permeability, and improve the strength and uniformity of the alloy through the coordinated cooperation of a specific proportion.
[0043] Furthermore, the preparation process of the magnetic core alloy material is simple and easy to implement, and the prepared magnetic core alloy material can adapt to existing production processes.
[0044] On the other hand, the present application also provides a magnetic alloy product, which includes the above-mentioned magnetic core alloy material or the magnetic core alloy material prepared by the above-mentioned method for preparing the magnetic core alloy material. DETAILED DESCRIPTION
[0045] For ease of understanding of the present application, the present application will be described more fully below, and preferred embodiments of the present application are provided. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0047] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0048] An embodiment of the present application provides a magnetic core alloy material. The element composition of the magnetic core alloy material, calculated by atomic mass percentage, includes:
[0049] Fe 60%~70%;
[0050] Si 14%~18%;
[0051] B 7%~12%;
[0052] Nb 2%~6%;
[0053] Cu 0.3%-2%;
[0054] Co 1%~4%;
[0055] Ni 1%~2%,
[0056] Mo 1%~2%.
[0057] It is understood that when a numerical range is disclosed herein, the above range is considered continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0058] It should be noted that the value range of Fe is "60% to 70%", which means that the minimum and maximum values in the range of 60% to 70% can be taken, as well as every value between the minimum and maximum values. Specific examples include, but are not limited to, the point values in the embodiments and the following point values: 60%, 60.1%, 60.2%, 60.3%, 60.4%, 60.5%, 60.6%, 60.7%, 60.8%, 60.9%, 61%, 61.1%, 61.2%, 61.3%, 61.4%, 61.5%, 61.6%, 61.7%, 61.8%, 61.9%, 62%, 62.1%, 62.2%, 62. 3%, 62.4%, 62.5%, 62.6%, 62.7%, 62.8%, 62.9%, 63%, 63.1%, 63.2%, 63.3%, 63.4%, 63.5%, 63.6%, 63.7%, 63.8%, 63.9%, 64%, 64.1%, 64.2%, 64.3%, 64.4%, 64.5%, 64.6%, 64.7%, 64.8%, 64.9%, 65% , 65.1%, 65.2%, 65.3%, 65.4%, 65.5%, 65.6%, 65.7%, 65.8%, 65.9%, 66%, 66.1%, 66.2%, 66.3%, 66.4%, 66.5%, 66.7%, 66.8%, 66.9%, 67%, 67.1%, 67.2%, 67.3%, 67.4%, 67.5%, 67.6%, 67.7%, 67.8%, 67.9%, 68%, 68.1%, 68.2%, 68.3%, 68.4%, 68.5%, 68.6%, 68.7%, 68.8%, 68.9%, 69%, 69.1%, 69.2%, 69.3%, 69.4%, 69.5%, 69.6%, 69.7%, 69.8%, 69.9% or 70%; or a range consisting of any two of these values, including, as examples, 65% to 70%.
[0059] Iron is the main basic element of magnetic core alloy materials and the main source of magnetism. It has an inherent magnetic moment and can be magnetized under the action of a magnetic field, thereby generating magnetism, providing basic magnetic properties for magnetic core alloy materials and being a key basic component for achieving high magnetic permeability.
[0060] The value range of Si is "14%~18%", which means that it can take the minimum and maximum values in the range of 14%~18%, as well as every value between the minimum and maximum values. Specific examples include, but are not limited to, 14%, 14.1%, 14.2%, 14.3%, 14.4%, 14.5%, 14.6%, 14.7%, 14.8%, 14.9%, 15%, 15.1%, 15.2%, 15.3%, 15.4%, 15.5%, 15.6%, 15.7%, 15.8%, 15.9%, 16%, 16.1%, 16.2%, 16.3%, 16.4%, 16.5%, 16.6%, 16.7%, 16.8%, 16.9%, 17%, 17.1%, 17.2%, 17.3%, 17.4%, 17.5%, 17.6%, 17.8%, 17.9% or 18%; or a range consisting of any two of these values, including, by way of example, 14.5% to 16.5%.
[0061] The addition of silicon to the core alloy material helps to improve the magnetic permeability. It can achieve this by affecting the movement of the ferromagnetic domain wall, making it easier for the domain wall to move under the action of the magnetic field, thereby enhancing the material's ability to respond to the magnetic field and improving the magnetic permeability.
[0062] The value range of B is "7%~12%", which means that it can take the minimum and maximum values in the range of 7%~12%, as well as every value between this minimum and maximum value. Specific examples include, but are not limited to, 7%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.6%, 7.7%, 7.8%, 7.9%, 8%, 8.1%, 8.2%, 8.3%, 8.4%, 8.5%, 8.6%, 8.8%, 8.9%, 9%, 9.1%, 9.2%, 9.3%, 9.4%, 9.5%, 9.6%, 9.7%, 9.8%, 9.9%, 10%, 10.1%, 10.2%, 10.3%, 10.4%, 10.5%, 10.6%, 10.7%, 10.8%, 10.9%, 11%, 11.1%, 11.2%, 11.3%, 11.4%, 11.5%, 11.6%, 11.7%, 11.8%, 11.9% or 12%; or a range consisting of any two of these values, including, by way of example, 8% to 10%.
[0063] Boron can refine the grains during the solidification process of the material. The fine grain structure helps to improve the magnetic properties of the magnetic core alloy material, because after the grains are refined, the movement of the magnetic domain wall is relatively easier, which is conducive to improving the magnetic permeability and making the performance of the magnetic core alloy material more uniform.
[0064] The value range of Nb is "2%~6%", which means the minimum and maximum values in the range of 2%~6%, and every value between the minimum and maximum values. Specific examples include, but are not limited to, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9% or 6%, or a range consisting of any two of these values.
[0065] Niobium has a grain refinement effect in the magnetic core alloy material, similar to boron. At the same time, it can also inhibit excessive grain growth during subsequent heat treatment and keep the grains small and uniform. A small and uniform grain structure is very important for improving the magnetic permeability of the magnetic core alloy material and ensuring the stability of the magnetic properties.
[0066] The value range of Cu is "0.3%~2%", which means the minimum and maximum values in the range of 0.3%~2%, and every value between the minimum and maximum values. Specific examples include but are not limited to 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%; or a range consisting of any two of these values.
[0067] Copper interacts with other elements and can promote grain growth during heat treatment or solidification of materials. Appropriate grain size is beneficial to the performance of magnetic core alloy materials. It can affect the mobility of magnetic domain walls to a certain extent, and thus affect magnetic performance indicators such as magnetic permeability.
[0068] The value range of Co is "1%~4%", which means the minimum and maximum values in the range of 1%~4%, and every value between the minimum and maximum values. Specific examples include but are not limited to 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9% or 4%; or a range consisting of any two of these values.
[0069] Cobalt is an element with high magnetic permeability. When added to the magnetic core alloy material, it can work synergistically with elements such as iron to further improve the overall magnetic permeability of the material. It can enhance the material's ability to respond to the magnetic field, so that under the same magnetic field strength, the material can produce a stronger magnetization effect, thereby improving the magnetic permeability.
[0070] The value range of Ni is "1%~2%", which means the minimum and maximum values in the range of 1~2%, and every value between the minimum and maximum values. Specific examples include but are not limited to 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%; or a range consisting of any two of these values.
[0071] Nickel is also a magnetic element. It can enhance the overall magnetism of the magnetic core alloy material and improve the magnetic permeability by working in synergy with iron, cobalt, etc. It can improve the magnetic properties by changing the magnetic domain structure inside the material, making the material easier to be magnetized under the action of the magnetic field.
[0072] The value range of Mo is "1%~2%", which means the minimum and maximum values in the range of 1%~2%, and every value between the minimum and maximum values. Specific examples include but are not limited to 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%; or a range consisting of any two of these values.
[0073] Molybdenum also plays a role in refining the grains in the magnetic core alloy material. Fine grains help improve the magnetic properties of the magnetic core alloy material, making it easier for the magnetic domain wall to move, thereby increasing the magnetic permeability and making the performance of the magnetic core alloy material more uniform.
[0074] The above-mentioned components cooperate with each other through a specific ratio, which strengthens the magnetic properties, enhances the magnetic induction intensity and magnetic permeability, and improves the strength and uniformity of the alloy.
[0075] In some embodiments, the element composition of the magnetic core alloy material comprises, by atomic mass percentage:
[0076] Fe 64%~68%;
[0077] Si 15%~16%;
[0078] B 9%~11%;
[0079] Nb 3%~5%;
[0080] Cu 0.5%-2%;
[0081] Co 2%~3%;
[0082] Ni 1.5%~1.8%;
[0083] Mo 1.5%~1.8%.
[0084] In some embodiments, the magnetic core alloy material is a nanocrystalline soft magnetic alloy material; when the frequency changes from 1 kHz to 10 kHz, the magnetic permeability change rate of the magnetic core alloy material is less than 0.5%.
[0085] An embodiment of the present application further provides a method for preparing a magnetic core alloy material, comprising the following steps S10 to S40.
[0086] S10, weighing raw materials according to the element composition ratio of the magnetic core alloy material, placing them in a smelting furnace for a first smelting treatment, and casting to obtain an alloy ingot.
[0087] It should be noted that the melting furnace used above can be an induction melting furnace commonly used in the art, such as a medium frequency vacuum induction furnace.
[0088] It can be understood that under vacuum conditions, alloy elements can be more fully mixed during the smelting process, which improves the uniformity of the alloy composition. The vacuum environment effectively avoids the contact between the metal material and the outside world, reduces the pollution of impurities and gases, improves the purity of the alloy, and helps to improve the quality of the alloy.
[0089] In some of the embodiments, the conditions of the first smelting treatment are: smelting at a vacuum degree of 0.5Pa-0.8Pa and a temperature of 1450°C-1550°C for 2h-4h.
[0090] Specifically, after ensuring that the alloy elements are fully and evenly mixed, the smelted alloy melt is poured into a rotary casting plate equipped with an efficient cooling system to form an alloy ingot.
[0091] S20, after cooling the alloy ingot, performing a second smelting treatment to obtain an alloy melt; the temperature of the second smelting treatment is lower than the temperature of the first smelting treatment.
[0092] It can be understood that through secondary smelting, the microstructure of the alloy can be further optimized, the ingot can be further refined and adjusted, the content of volatile impurities can be reduced, the impact of impurities on the performance of the ingot can be reduced, the organizational structure of the ingot can be optimized, the uniformity and density of the ingot can be improved, and the quality of the ingot can be further improved.
[0093] In some embodiments, the temperature of the second smelting process is 1100°C-1250°C.
[0094] In some embodiments, the second smelting treatment lasts for 50 min to 60 min.
[0095] S30, forming and cooling the alloy melt to obtain an alloy strip.
[0096] Specifically, the above-mentioned forming cooling is achieved by rapid spraying and high-speed rotating copper rollers.
[0097] In some of the embodiments, the alloy melt is rapidly sprayed through a bottom nozzle onto a copper roller equipped with an enhanced quenching device and rotating at a high speed, the distance between the nozzle and the copper roller is controlled to adjust the strip thickness, and the width is controlled by the nozzle.
[0098] In some embodiments, the alloy strip has a thickness of 15 μm to 20 μm.
[0099] In some embodiments, the width of the alloy strip is 5 mm to 30 mm.
[0100] It can be understood that the nanocrystalline soft magnetic alloy strip made by the above method can significantly improve the production speed of the strip through rapid spraying and high-speed rotating copper rollers. Accurate control of the distance between the nozzle and the copper roller helps to ensure the uniformity and consistency of the strip thickness. The enhanced quenching device can quickly reduce the temperature of the molten steel, promote rapid solidification of the material, reduce structural defects, and improve the performance of the material.
[0101] S40, subjecting the alloy strip to heat treatment and performing magnetization treatment during the heat treatment process to obtain a magnetic core alloy material.
[0102] In some embodiments, the heat treatment step includes the following steps S41 to S44.
[0103] S41, firstly, in a vacuum state, heat to 460℃~480℃ and keep warm for 1.5h for pretreatment;
[0104] S42, performing magnetization treatment at a temperature of 460°C to 480°C for a time of 60min to 120min;
[0105] S43, perform the first heating treatment, raise the temperature to 500°C~550°C, and keep it for 1h~3h;
[0106] S44, conduct a second heating treatment, raise the temperature to 560℃~580℃, and keep it warm for 1h~3h.
[0107] In some of the embodiments, the heating rate during the first heating process is (5-10)°C / min.
[0108] In some of the embodiments, the heating rate during the second heating process is (5-10)°C / min.
[0109] The preparation process of the magnetic core alloy material is simple and easy to implement. The prepared magnetic core alloy material optimizes the microstructure of the alloy, reduces the content of volatile impurities, improves the uniformity and density of the ingot, and improves the uniformity and consistency of the strip thickness, and can adapt to existing production processes.
[0110] An embodiment of the present application further provides a magnetic alloy product, wherein the magnetic alloy product includes the magnetic core alloy material or the magnetic core alloy material prepared by the preparation method of the magnetic core alloy material.
[0111] The above-mentioned magnetic core alloy material and its preparation method, when used in the preparation of magnetic alloy products, have excellent high magnetic permeability characteristics and can meet the requirements of equipment high efficiency, energy saving and environmental protection.
[0112] In some of the examples, the magnetic alloy products include, but are not limited to, transformer devices, inductor devices, mutual inductor devices, wireless charging devices, and magnetic recording devices.
[0113] In order to make the purpose, technical solutions and advantages of the present invention more concise and clear, the present invention is described with the following specific embodiments, but the present invention is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present invention, which can be used to describe the present invention and cannot be understood as limiting the scope of the present invention. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0114] In order to better illustrate the present invention, the content of the present invention is further described below in conjunction with embodiments.
[0115] Example 1
[0116] (1) Clean the Fe, Si, B, Nb, Cu, Co, Ni and Mo prepared in the above manner by spray cleaning, in which the dirt is washed away by a pressurized liquid jet to remove the slight dirt attached to the surface.
[0117] (2) Place the above ingredients in a medium frequency vacuum induction furnace and melt them at 1500°C. The vacuum degree is maintained at 0.5 Pa to ensure that the alloy is not affected by impurities such as oxygen during the melting process. The melting time is 3 hours to ensure that the alloy is fully melted and homogenized.
[0118] (3) The alloy is cooled to room temperature using a cooling device, and then the alloy ingot is placed in the crucible of the belt spraying machine for secondary smelting. The smelting temperature is set to 1200°C, which is slightly lower than the temperature of the initial smelting, which helps to further homogenize and refine the alloy structure. The smelting time is 60 minutes to ensure that the alloy is fully melted and homogenized again.
[0119] (4) After smelting, the molten steel is passed through a tundish preheated to above the molten steel temperature, and is quickly sprayed through the bottom nozzle onto a copper roller equipped with an enhanced quenching device and rotating at high speed. The distance between the nozzle and the copper roller is controlled to adjust the strip thickness. The distance is 0.5 mm, which can ensure that the strip thickness is between 15-20 microns. The width is controlled by the nozzle, and the controlled width is 20 mm, obtaining a nanocrystalline soft magnetic alloy strip.
[0120] (5) The nanocrystalline soft magnetic alloy strip is precisely wound into an iron core, which is then placed in a vacuum heat treatment furnace for multi-stage heat treatment:
[0121] a. Slowly raise the temperature of the vacuum heat treatment furnace to 475℃ and keep it at this temperature for 1.5 hours to preheat and homogenize the alloy structure.
[0122] b. When the temperature reaches 475℃, push the furnace into a strong magnetic field with the magnetic field direction strictly along the axial direction of the iron core. Keep the temperature between 475-485℃ for 1.5 hours and perform magnetic field annealing to enhance the magnetic properties of the alloy.
[0123] c. After exiting the magnetic field, continue to raise the temperature to 500°C and keep it for 2 hours for homogenization treatment to further eliminate stress and defects inside the alloy.
[0124] d. Finally, slowly raise the temperature to 560°C and keep it for 2 hours for final heat treatment. This temperature is slightly higher than the previous treatment temperature, which helps to optimize the magnetic properties of the material. Then close the vacuum heat treatment furnace and cool it naturally to room temperature to obtain the magnetic core alloy material.
[0125] (6) Test the physical and chemical properties of the prepared magnetic core alloy material:
[0126] 1. The test of magnetic induction intensity is carried out by using a vibrating sample magnetometer (VSM) or a fluxmeter. These devices can measure the magnetic induction intensity of a material in a magnetic field.
[0127] 2. The magnetic permeability test is carried out using an impedance analyzer or an LCR bridge. These devices can measure the magnetic permeability of materials in an AC magnetic field.
[0128] 3. The saturation magnetization intensity is tested using a vibrating sample magnetometer (VSM).
[0129] Please see Table 2 for specific results.
[0130] Embodiment 2~6
[0131] Examples 2 to 6 are substantially the same as Example 1, except for the components in Table 1.
[0132] Other conditions and parameters are the same as those in Example 1. Please see Table 2 for specific test results.
[0133] Comparative Example 1~2
[0134] Comparative Examples 1-2 are substantially the same as Example 1, except that the elemental composition of the magnetic core alloy material in Comparative Examples 1-2 is as shown in Table 1.
[0135] Other conditions and parameters are the same as those in Example 1. Please see Table 2 for specific test results.
[0136] The elemental composition of the magnetic material in each embodiment and comparative example is shown in Table 1.
[0137] Table 1
[0138]
[0139] Please see Table 2 for the performance test results of each embodiment and comparative example.
[0140] Table 2
[0141]
[0142] The test of the magnetic core alloy material obtained in the data in Table 2 shows that: compared with the magnetic core alloy material in the comparative example, the magnetic core alloy material in the embodiment of the present application has stronger magnetic induction intensity and magnetic permeability, and the strength and uniformity of the alloy are more excellent.
[0143] The magnetic core alloy material in Examples 1 to 10 of the present application has a magnetic permeability change rate of less than 0.5% within a frequency range of 1 kHz to 10 kHz, exhibiting excellent high magnetic permeability characteristics.
[0144] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0145] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A magnetic core alloy material, characterized in that: The element composition of the magnetic alloy material includes, by mass percentage: Fe 60%~70%; Si 14%~18%; B 7%~12%; Nb 2%~6%; Cu 0.3%-2%; Co 1%~4%; Ni 1%~2%; Mo 1%~2%.
2. The magnetic core alloy material according to claim 1, characterized in that: The element composition of the magnetic core alloy material includes, by mass percentage: Fe 64%~68%; Si 15%~16%; B 9%~11%; Nb 3%~5%; Cu 0.5%-2%; Co 2%~3%; Ni 1.5%~1.8%; Mo 1.5%~1.8%.
3. The magnetic core alloy material according to claim 1 or 2, characterized in that: The magnetic core alloy material is a nanocrystalline soft magnetic alloy material; when the frequency changes from 1 kHz to 10 kHz, the magnetic permeability change rate of the magnetic core alloy material is less than 0.5%.
4. The method for preparing the magnetic core alloy material according to any one of claims 1 to 3, characterized in that: The steps include: Weighing raw materials according to the element composition ratio of the magnetic core alloy material and placing them in a smelting furnace for a first smelting treatment, and casting to obtain an alloy ingot; After the alloy ingot is cooled, a second smelting treatment is performed to obtain an alloy melt; the temperature of the second smelting treatment is lower than the temperature of the first smelting treatment; The alloy melt is formed and cooled to obtain an alloy strip; The alloy strip is subjected to heat treatment and magnetization treatment during the heat treatment process to obtain a magnetic core alloy material.
5. The method for preparing a magnetic core alloy material according to claim 4, characterized in that: The conditions of the first smelting treatment are: smelting at a vacuum degree of 0.5 Pa to 0.8 Pa and a temperature of 1450° C. to 1550° C. for 2 h to 4 h.
6. The method for preparing a magnetic core alloy material according to claim 4, characterized in that: The temperature of the second smelting treatment is 1100°C to 1250°C; And / or, the time of the second smelting treatment is 50min~60min.
7. The method for preparing a magnetic core alloy material according to claim 4, characterized in that: The thickness of the alloy strip is 15 μm to 20 μm, and the width of the alloy strip is 5 mm to 30 mm.
8. The method for preparing a magnetic core alloy material according to any one of claims 4 to 7, characterized in that: The heat treatment step comprises the following steps: First, in a vacuum state, heat to 460℃~480℃ and keep it for 1.5h for pretreatment; The magnetization treatment is carried out at a temperature of 460°C to 480°C, and the magnetization time is 60min to 120min; Carry out the first heating treatment, raise the temperature to 500℃~550℃, and keep it for 1h~3h; Carry out the second heating treatment, raise the temperature to 560℃~580℃, and keep it for 1h~3h.
9. The method for preparing a magnetic core alloy material according to claim 8, characterized in that: The heating rate during the first heating treatment is (5-10)°C / min; And / or, the heating rate during the second heating treatment is (5-10)°C / min.
10. A magnetic alloy product, characterized in that: The magnetic alloy product comprises the magnetic core alloy material as described in any one of claims 1 to 3 or the magnetic core alloy material prepared by the preparation method of the magnetic core alloy material as described in any one of claims 4 to 9.